The role of CD14 during resolution of experimentally induced Staphylococcus aureus and Streptococcus uberis mastitis - Sladek, Z; Rysanek, D (Comparative immunology, microbiology and infectious diseases, 2006)
This study was undertaken to investigate the time course of surface expression of CD14 on neutrophils and macrophages and to determine their association with resolution of inflammatory responses during Staphylococcus aureus and Streptococcus uberis experimental mastitis. Infections of the mammary gland induce a local immune response characterized by an increase in the total counts of CD14+ neutrophils and CD14+ macrophages particularly. On the other hand, resolution is accompanied by an increase in relative counts of CD14+ neutrophils, CD14+ vacuolized macrophages and apoptotic neutrophils. Following the immune reaction of mammary gland against Gram-negative/positive bacteria is very similar. Between the apoptotic and CD14+ neutrophils a high correlation was measured during the whole experimental period (S. aureus: r=0.64; S. uberis: r=0.61; P<0.05). Using anti-CD14 monoclonal antibodies in vitro suggested the involving of the CD14 surface receptor in recognition of apoptotic neutrophils by macrophages.
Keywords: Staphylococcal Infections; Staphylococcus aureus; lipopolysacharidové receptory; Lipopolysaccharide Receptors; Streptococcus; stafylokokové infekce; Female; makrofágy; neutrofily; zvířata; streptokokové infekce; apoptóza; Mastitis, Bovine; Streptococcal Infections; fagocytóza; Cattle; ženské pohlaví; Flow Cytometry; Neutrophils; skot; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; průtoková cytometrie; mastitida skotu; Animals; Macrophages; Phagocytosis; Apoptosis